PELATIHAN PEMBUATAN PUPUK ORGANIK CAIR (POC) SEBAGAI ALTERNATIF PEMENUHAN UNSUR HARA DALAM MENGHADAPI KELANGKAAN PUPUK KIMIA DI DESA AJUNG JEMBER - Wilujeng, Elly Daru Ika; Rosyadi, Moch. Adnan; Alwi, Annisa; Kusumaningtyas, Rizky Nirmala; Aisyah, Mahindra Dewi Nur; Alif, Trisnani; Rusdiarti (Program Studi Agronomi Fakultas Pertanian Universitas Jember, 2024)
Ajung Village is one of the villages in Jember where the majority are farmers and generally depend on obtaining chemical fertilizers. On the other hand, there are youth who are members of Karang Taruna Persada Muda who have the potential to be developed through various activities, considering that currently, their activities are incidental. Therefore, training in making Liquid Organic Fertilizer (LOF) is a useful activity for developing youth and the resulting product can reduce dependence on chemical fertilizers. The methods used in this training activity are delivery of material and discussion, direct practice, and evaluation through questionnaires (pre and post-test). The evaluation results show that the making of LOF training increased the knowledge and insight of Karang Taruna youth in Ajung Village. It is hoped that in the future further training will be provided regarding marketing and manufacturing of other agricultural products.